PERFORMANCE EVALUATION OF VERI-Q RED HAEMOGLOBIN METER FOR POINT-OF-CARE HAEMOGLOBIN AND PACKED CELL VOLUME ESTIMATIONS - Apollos, Vivian; Jacob, Ransom; Jeremiah, Zaccheaus (Sanamed, 2024)
Introduction: Haemoglobin (Hb) and packed cell volume (PCV) are tests used in the assessment of anaemia. The Veri-Q haemoglobin meter is a new device in the point-of-care market used for the quantitative measurement of haemoglobin and packed cell volume. This study aimed to evaluate the performance of the Veri-Q haemoglobin meter for the assessment of haemoglobin and packed cell volume. Materials and Methods: Haemoglobin and packed cell volume estimations of one hundred and eleven participants were determined using the Veri-Q Red haemoglobin meter and statistically compared with those obtained from the conventional method (gold standard). Results: One hundred and eleven undergraduate students participated in this study, of whom 72 (64.9%) were females and 39 (35.1%) were males. The mean haemoglobin values calculated using the Veri-Q haemoglobin meter (11.97 ± 1.95 g/dl) were significantly lower than the values obtained with the conventional method (12.35 ± 1.66 g/dl) (t= 4.7549; p=0.0001). Similar results were obtained with packed cell volume estimation. The performance indices of the Veri-Q haemoglobin meter were as follows: sensitivity (75.41% for Hb and 77.05% for PCV), specificity (28.0% for Hb and PCV), positive predictive value (PPV) (56.1% for Hb and 56.63% for PCV), negative predictive value (48.28% for Hb and 50% for PCV). The prevalence of anemia in this study was 54.05%. Positive Likelihood Ratio (1.05 for Hb and 1.07 for PCV), Negative Likelihood Ratio (0.88 for Hb and 0.82 for PCV), Accuracy (54.05% for Hb and 54.95% for PCV). The Receiver Operative Characteristics (ROC) Area Under Curve (AUC) was 0.996 for Hb and 0.984 for PCV. A significant but weak positive correlation was found to exist between haemoglobin estimations using conventional and Veri-Q methods (r=0.3013, P =0.01); PCV (R=0.2512, P =0.07). The sensitivity of the device can be described as moderate while the specificity is low. The accuracy of the device is just average. Conclusion: The Veri-Q haemoglobin meter demonstrates an average level of accuracy and a high AUC, making it potentially useful for field epidemiological studies.